Between politics and business: Boardroom decision making in state‐owned Indonesian enterprises. (16th January 2019) - Apriliyanti, Indri Dwi; Randøy, Trond
Abstract: Research Question/Issue: A significant part of the world's economy is controlled by state‐owned enterprises, and there is a lack of research on how the interplay between politics and business plays out in the boardroom. We address this issue by analyzing boardrooms' decision outcomes as they relate to the role of boardroom power distribution, members' motivation, and decision‐making approach. Research Findings/Insights: On the basis of information from a sample of 22 state‐owned Indonesian enterprises, we found that a decision outcome in a boardroom is influenced by three factors: the motivation and decision‐making approach of individual board members and the distribution of power in the boardroom. We also found that, in several cases, board members are powerless decision makers, as the decision‐making process in the boardroom is controlled by the government and politicians. Theoretical/Academic Implications: This study contributes to the understanding of the inner working processes in emerging‐market boardrooms, and we build a theory‐driven typology of boards' decision outcomes. Practitioner/Policy Implications: This paper highlights the nature of political interactions within the boards of state‐owned enterprises, and we recommend that state‐owned enterprises seek board members who are knowledgeable and rationally motivated, as well as seek a (more) equal power distribution among board members. Politicking and political interference can lower the quality of boards' decisions.